Histopathologic Changes Induced by Intense Pulsed Light in the Treatment of Poikiloderma of Civatte - Scattone, Luciane; de Avelar Alchorne, Mauricio M.; Michalany, Nilceo; Miot, Hélio Amante [UNESP]; Higashi, Viviane S. (Wiley-Blackwell, 2012)
Background The clinical efficacy of intense pulsed light (IPL) in the treatment of poikiloderma of Civatte (PC) is well documented, but little is known about microscopic changes. Objective To analyze histopathologic findings on the necks of individuals with PC after IPL therapy. Materials and Methods Fourteen patients with PC on the neck underwent three monthly sessions of IPL. Biopsies and clinical photographs were taken before and 60 similar to days after treatment. A dermatopathologist analyzed histopathologic slides stained with hematoxylin and eosin, Masson's trichrome, Verhoeff-van Gieson and Fontana-Masson or processed for CD-34 immunohistochemistry. The slides also underwent digital image analysis. Clinical results were based on the analysis of the pictures by three dermatologists and on patient satisfaction. Results Intense pulsed light treatment resulted in more-homogeneous melanin distribution; a greater number of fibroblasts and nonfragmented elastic fibers; and greater density (p similar to=similar to.01), color intensity (p similar to=similar to.02), number and thickness of the collagen bundles. No significant changes in vessels number or diameters were observed. Clinical results were positive in 92.9% of the cases. Conclusion IPL treatment of PC induced a more-homogeneous distribution of melanin and increased nonfragmented elastic fibers, collagen density, and intensity. These changes were related to clinical improvement.